STUDI KORELASI KOMPETENSI PEDAGOGIK DAN KOMPETENSI KEPRIBADIAN GURU BAHASA ARAB DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI MTsN DONDO KABUPATEN TOLITOLI - Muhammad Nur Asmawi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
This research reveals a pedagogical competence and personal competence of teachers of Arabic in Dondo MTsN Tolitoli. Pedagogical competence is a skill or ability that must be mastered a teacher in viewing characteristics of students of various aspects of their life. Personal competence of teachers is the ability of personality steady, stable, mature, wise and dignified, become role models for students and noble. From this research known correlation Pedagogic Competence and Personality of Teachers of Arabic on the students motivation MTsN Dondo amounted to 0.752. This shows that a strong correlation between teachers' pedagogical competence and personality Arabic simultaneously on motivation to learn a students Dondo. While the level of significance of the correlation coefficient of 0.000 one-sided, because the probability is much below 0.05 the correlation pedagogical competence and personality Arabic teacher with student motivation MTsN Dondo was significant